Sacral co‐ossification in dinosaurs: The oldest record of fused sacral vertebrae in Dinosauria and the diversity of sacral co‐ossification patterns in the group. Issue 4 (9th November 2020) - Moro, Débora; Kerber, Leonardo; Müller, Rodrigo T.; Pretto, Flávio A.
Abstract: The fusion of the sacrum occurs in the major dinosaur lineages, i.e. ornithischians, theropods, and sauropodomorphs, but it is unclear if this trait is a common ancestral condition, or if it evolved independently in each lineage, or even how or if it is related to ontogeny. In addition, the order in which the different structures of the sacrum are fused, as well as the causes that lead to this co‐ossification, are poorly understood. Herein, we described the oldest record of fused sacral vertebrae within dinosaurs, based on two primordial sacral vertebrae from the Late Triassic of Candelária Sequence, southern Brazil. We used computed microtomography (micro‐CT) to analyze the extent of vertebral fusion, which revealed that it occurred only between the centra. We also assessed the occurrence of sacral fusion in Dinosauria and close relatives. The degree of fusion observed in representatives of the major dinosaur lineages suggested that there may be a sequential pattern of fusion of the elements of the sacrum, more clearly observed in Sauropodomorpha. Our analyses suggest that primordial sacral vertebrae fuse earlier in the lineage (as seen in Norian sauropodomorphs). Intervertebral fusion is observed to encompass progressively more vertebral units as sauropodomorphs evolve, reaching up to five or more fully fused sacrals in Neosauropoda. Furthermore, the new specimen described here indicates that the fusion of sacral elements occurred early in the evolution of dinosaurs. Factors such as ontogeny and the increase in body size, combined with the incorporation of vertebrae to the sacrum may have a significant role in the process and in the variation of sacral fusion observed. Abstract : This paper describes the oldest record of fused sacral vertebrae for Dinosauria, based on two primordial sacrals from the Brazilian Upper Triassic. We also review the occurrence of sacral fusion in Dinosauria and close relatives. The new specimen indicates that sacral fusion occurred early in the evolution of dinosaurs and our review suggests that, at least in Sauropodomorpha, the primordial sacrals fuse prior to the additional sacral vertebrae, which fuse later along the lineage.